APLIKASI PENGOLAHAN CITRA PADA RASPBERRY PI UNTUK MEMBEDAKAN BENDA BERDASARKAN WARNA DAN BENTUK - Figur Humani; Kusworo Adi; Catur Edi Widodo (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Computer technology has been developed to support problem solving in human life. Nowadays, minicomputer has been the focus of development for its practicality. The role of technology has progressed from word processing programs to digital image processing programs. Digital image processing is one of technology processing using computer vision. The role of digital image processing is a common process in industries and has been use to increase their productivity. One of those utilizations is image processing in beverage industries to detect the number of empty bottles in crates. Digital processing which supports industries has been a factor to increase productivity. The innovation in the research was utilizing minicomputer called raspberry to be integrated with image processing system and motor servo control. The result is a system to distinguish various objects based on their colors and shapes using image processing system on raspberry based on open CV and to control motor servo to classify objects. The accuracy to classify red circular objects was 92,5% , for green circular objects was 97,5% , and red rectangular objects was 97,5% by using camera resolution 480x320.